Streaking and Wigner time delays in photoemission from atoms and surfaces - Zhang, Chang-Hua; Thumm, Uwe P. E. (My University, 2011)
Streaked photoemission metrology allows the observation of an apparent relative time delay between the detection of photoelectrons from different initial electronic states. This relative delay is obtained by recording the photoelectron yield as a function of the delay between an ionizing ultrashort extended ultraviolet pulse and a streaking infrared (IR) pulse. Theoretically, photoemission delays can be defined based on (i) the phase shift the photoelectron wave function accumulates during the release and propagation of the photoelectron (“Wigner delay”) and, alternatively, (ii) the streaking trace in the calculated photoemission spectrum (“streaking delay”). We investigate the relation between Wigner and streaking delays in the photoemission from atomic and solid-surface targets. For solid targets and assuming a vanishing IR skin depth, both Wigner and streaking delays can be interpreted as an average propagation time needed by photoelectrons to reach the surface, while the two delays differ for nonvanishing skin depths. For atomic targets, the difference between Wigner and streaking delays depends on the range of the ionic potential.
Keywords: Streaked photoemission metrology; Photoemission; Wigner delay; Streaking delay